Cascading effects of predator richness. Issue 10 (1st December 2008) - Bruno, John F; Cardinale, Bradley J
Abstract : Biologists have long known that predators play a key role in structuring ecological communities, but recent research suggests that predator richness – the number of genotypes, species, and functional groups that comprise predator assemblages – can also have cascading effects on communities and ecosystem properties. Changes in predator richness, including the decreases resulting from extinctions and the increases resulting from exotic invasions, can alter the composition, diversity, and population dynamics of lower trophic levels. However, the magnitude and direction of these effects are highly variable and depend on environmental context and natural history, and so are difficult to predict. This is because species at higher trophic levels exhibit many indirect, non‐additive, and behavioral interactions. The next steps in predator biodiversity research will be to increase experimental realism and to incorporate current knowledge about the functional role of predator richness into ecosystem management.